Individual differences in infancy research: Letting the baby stand out from the crowd. (4th May 2020) - Pérez‐Edgar, Koraly; Vallorani, Alicia; Buss, Kristin A.; LoBue, Vanessa
Abstract: Within the developmental literature, there is an often unspoken tension between studies that aim to capture broad scale, fairly universal nomothetic traits, and studies that focus on mechanisms and trajectories that are idiographic and bounded to some extent by systematic individual differences. The suitability of these approaches varies as a function of the specific research interests at hand. Although the approaches are interdependent, they have often proceeded as parallel research traditions. The current review notes some of the historical and empirical bases for this divide and suggests that each tradition would benefit from incorporating both methodological approaches to iteratively examine universal (nomothetic) phenomena and the individual differences (idiographic) factors that lead to variation in development. This work may help isolate underlying causal mechanisms, better understand current functioning, and predict long‐term developmental consequences. In doing so, we also highlight empirical and structural issues that need to be addressed to support this integration.